Foxo1‐induced miR‐92b down‐regulation promotes blood‐brain barrier damage after ischaemic stroke by targeting NOX4. Issue 11 (6th May 2021) - Shen, Jian; Li, Ganglei; Zhu, Yu; Xu, Qingsheng; Zhou, Hengjun; Xu, Kangli; Huang, Kaiyuan; Zhan, Renya; Pan, Jianwei
Abstract: The blood‐brain barrier (BBB) damage is a momentous pathological process of ischaemic stroke. NADPH oxidases 4 (NOX4) boosts BBB damage after ischaemic stroke and its expression can be influenced by microRNAs. This study aimed to probe into whether miR‐92b influenced the BBB damage after ischaemic stroke by regulating NOX4 expression. Here, miR‐92b expression was lessened in the ischaemic brains of rats and oxygen‐glucose deprivation (OGD)‐induced brain microvascular endothelial cells (BMECs). In middle cerebral artery occlusion (MCAo) rats, miR‐92b overexpression relieved the ameliorated neurological function and protected the BBB integrity. In vitro model, miR‐92b overexpression raised the viability and lessened the permeability of OGD‐induced BMECs. miR‐92b targeted NOX4 and regulated the viability and permeability of OGD‐induced BMECs by negatively modulating NOX4 expression. The transcription factor Foxo1 bound to the miR‐92b promoter and restrained its expression. Foxo1 expression was induced by OGD‐induction and its knockdown abolished the effects of OGD on miR‐92b and NOX4 expressions, cell viability and permeability of BMECs. In general, our findings expounded that Foxo1‐induced lessening miR‐92b boosted BBB damage after ischaemic stroke by raising NOX4 expression.